Stoichiometric characteristics drive the soil aggregate stability after 5 years of vegetation restoration in China - Kan, Haiming; Xu, Hengkang; Zhang, Guofang; Chen, Chao; Pang, Zhuo; Fan, Xifeng; Wu, Juying (Frontiers in Ecology and Evolution, 2023)
Soil stoichiometric characteristics and aggregate stability are affected by vegetation restoration in degraded land. Yet, it is not known that how the aggregate stability is related to soil stoichiometric characteristics under different vegetation restorations. A 5-year in situ experiment was conducted to investigate the effects of vegetation restoration on the composition, stability and stoichiometric properties of soil aggregates. In the northwest part of Beijing, Bromus inermis Leyss. and Medicago sativa L. were planted in a typical area of desertification, and natural restoration was used as control. Boosted regression trees (BRTs) were applied to partition the factors that control aggregate stability. The results showed that the mean weight diameter (MWD) of soil water-stable aggregates under natural restoration (CK) and Medicago sativa L. sowing treatments (AF) was significantly higher than that under the restoration of the Bromus inermis Leyss. sowing treatments (SB). Compared with CK, AF significantly increased the geometric mean diameter (GMD) water stable aggregates, while SB showed the opposite result. AF significantly increased the proportion of soil aggregates >2 mm compared with CK. AF could improve the stability of soil aggregates by increasing the proportion of large aggregates. For the stoichiometric characteristics of the aggregates, AF increased significantly the value of C/P in 0.053−0.125mm particle size aggregates in all soil layers. The MBC/MBN ratio aggregates at depths of 0-10cm and 10-20cm was also significantly increased in the treatment of AF. The BRTs indicated that stoichiometric ratio is the main factor driving the stability of soil aggregates rather than microbial community characteristics and soil nutrients. The C/P is the main driving factor affecting the MWD, in which the overall stoichiometric influence accounts for 46%, followed by the microbial influence of 36%. For the GMD, MBC/MBN is the main driving factor, and the stoichiometric influence accounts for 94%. Our findings indicate that AF is beneficial to the stability of deep soil aggregates, and their stoichiometric characteristics of soil are the key factors affecting the stability of soil aggregates.